2011
DOI: 10.2319/052710-233.1
|View full text |Cite
|
Sign up to set email alerts
|

Class II correction improves nocturnal breathing in adolescents

Abstract: Objective: To examine modifications in sleep pattern and in craniofacial morphology of adolescents with mandibular retrognathism. Materials and Methods: Sixteen subjects at maximum pubertal growth (12.6 years [611.5 months]) were selected and treated for 12 months with maxillary expansion and mandibular advancement with a Herbst appliance. Cephalometric radiography and magnetic resonance imaging were obtained prior to and after treatment and were compared using the paired Student's t-test or the nonparametric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
73
0
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(90 citation statements)
references
References 19 publications
7
73
0
8
Order By: Relevance
“…Similar to our observation, Ozbek et al 11 also noted a 2.08 6 0.59 mm increase in the DOP following Class II treatment with the Harvold activator. Schutz et al, 17 however, reported 3.2 mm improvement of the posterior airway space following maxillary expansion and Herbst therapy in Class II subjects. They explained that Herbst appliance therapy displaced the mandible and hyoid bone forward and caused anterior traction of the tongue and increased the posterior airway space.…”
Section: Comparison Of Mean Differencesmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to our observation, Ozbek et al 11 also noted a 2.08 6 0.59 mm increase in the DOP following Class II treatment with the Harvold activator. Schutz et al, 17 however, reported 3.2 mm improvement of the posterior airway space following maxillary expansion and Herbst therapy in Class II subjects. They explained that Herbst appliance therapy displaced the mandible and hyoid bone forward and caused anterior traction of the tongue and increased the posterior airway space.…”
Section: Comparison Of Mean Differencesmentioning
confidence: 99%
“…They explained that Herbst appliance therapy displaced the mandible and hyoid bone forward and caused anterior traction of the tongue and increased the posterior airway space. 17 However, Kinzinger et al 16 recommended that treatment of Class II malocclusion by functional mandibular advancer and Herbst appliance was ineffective in preventing breathing problems in patients who were at risk. The DHP was marginally improved in our untreated Class II subjects and in those subjects in whom the Class II malocclusion was corrected by MPA-IV, but it was significantly improved in twin-block subjects.…”
Section: Comparison Of Mean Differencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Eventually, the main objective of our study, i.e., subsequent effects of these appliances on the dimensions of pharyngeal airways, will be addressed. Having reviewed the literature, there are very few published studies [4,[10][11][12][13][14] that have investigated the effect of functional appliances on the dimensions of awake pharyngeal airways. Of these studies, four have included either headgear [4,10,12] or maxillary expansion [11] appliances in combination with functional appliances, and the other two studies have used only removable [13] The sample was then divided into two groups.…”
Section: Introductionmentioning
confidence: 99%
“…Having reviewed the literature, there are very few published studies [4,[10][11][12][13][14] that have investigated the effect of functional appliances on the dimensions of awake pharyngeal airways. Of these studies, four have included either headgear [4,10,12] or maxillary expansion [11] appliances in combination with functional appliances, and the other two studies have used only removable [13] The sample was then divided into two groups. The first group consisted of the subjects who were treated with removable functional appliances (Activator type), and the second group consisted of those who were treated with fixed functional appliances, Forsus Fatigue Resistant Device (FRD) (3M Unitek Corp, Monrovia, Calif).The sex and age distribution of the treatment groups are shown in Table 1.…”
Section: Introductionmentioning
confidence: 99%